Streptococcus pneumoniae Drugs Resistance in Acute Rhinosinusitis - Hao, Chong Jie; Chrysanti, Chrysanti; Nugrahadi, Trias (Althea Medical Journal, 2016)
Background: Acute rhinosinusitis that usually caused by Streptococcus pneumoniae becomes the reason why patients seek for medical care. Drugs resistance in Streptococcus pneumoniae is increasing worldwide. This study was conducted to determine drugs resistance of Streptococcus pneumonia from acute rhinosinusitis in Dr. Hasan Sadikin General Hospital.Methods: A descriptive laboratory study was conducted in JuneâOctober 2014 at the Laboratory of Microbiology Faculty of Medicine Universitas Padjadjaran. The sample was taken using nasopharyngeal swabbing from 100 acute rhinosinusitis patients in Dr. Hasan Sadikin General Hospital and planted on tryptic soy agar containing 5% sheep blood and 5 Î¼g/ml of gentamicin sulphate and then incubated in 5% CO2 incubator at 37Â°C for 24 hours. The identification of Streptococcus pneumonia was performed by optochin test. The susceptibility test against Streptococcus pneumoniae was done using disk diffusion method.The antibiotic disks were trimethoprim-sulfamethoxazole, oxacillin, levofloxacin, azithromycin, and doxycycline.Results: Out of 100 samples, 8 of them were tested positive for Streptococcus pneumoniae. Three of Streptococcus pneumoniae isolates died with unknown reason after it were stored at -80 .The drugs resistance test showed the resistance of Streptococcus pneumonia to oxacillin, azithromycin and trimethoprim were 6, whereas levofloxacin and doxycycline are 4.Conclusions: Streptococcus pneumonia drugs resistance in acute rhinosinusitis shows the resistance of Streptococcus pneumoniae to oxacillin, azithromycin and trimethoprim are 6, whereas the resistance to levofloxacin and doxycycline are 4. [AMJ.2016;3(1):64â8]DOI:Â 10.15850/amj.v3n1.722